2016
DOI: 10.9720/kseg.2016.4.515
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Hydrochemical Characteristics of Natural Carbonated Water at Seoqwipo, Jeju Island

Abstract: C isotopes and noble gases isotopes (He, Ne) were analyzed to determine their recharge age, source of CO 2 gas and noble gases of carbonated hot spring water and carbonated-water samples collected in the Seoqwipo of the Jeju. The pH of the carbonated waters ranges from 6.21 to 6.84, and the high electrical conductivity range (1,928~4,720 µS/cm). Their chemical composition is classified as Mg(Ca, Na)-HCO 3 and Na(Ca, Mg)-HCO 3 types. As a result of the calculation of groundwater age using CFCs concentrations as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The Li concentration in the bottled waters from granitic and metamorphic rocks ranged from 0.58 to 27.9 µg/L (average 7.52 ± 7.18 µg/L, n = 22) and 11.6 to 14.8 µg/L (average 13.6 ± 1.31 µg/L, n = 5), respectively (Table 3, Figure 4). The water samples from metamorphic rocks had higher Li concentrations, similar to that of groundwater in Jeju Island, Korea, which is mostly composed of basaltic rocks (12.0 ± 20.0 µg/L, n = 11) [30]. By contrast, Hyun et al [31] reported significantly lower Li concentrations (0.6 µg/L) in Jeju groundwater (n = 258).…”
Section: Lithium (Li) and Vanadium (V)mentioning
confidence: 65%
“…The Li concentration in the bottled waters from granitic and metamorphic rocks ranged from 0.58 to 27.9 µg/L (average 7.52 ± 7.18 µg/L, n = 22) and 11.6 to 14.8 µg/L (average 13.6 ± 1.31 µg/L, n = 5), respectively (Table 3, Figure 4). The water samples from metamorphic rocks had higher Li concentrations, similar to that of groundwater in Jeju Island, Korea, which is mostly composed of basaltic rocks (12.0 ± 20.0 µg/L, n = 11) [30]. By contrast, Hyun et al [31] reported significantly lower Li concentrations (0.6 µg/L) in Jeju groundwater (n = 258).…”
Section: Lithium (Li) and Vanadium (V)mentioning
confidence: 65%